Spinoza, the Epicurean authority and utility in materialism - Vardoulakis, Dimitris (Spinoza studies., 2020)
By radically re-reading the 'Theological Political Treatise', Dimitris Vardoulakis argues that Spinoza's Epicurean influence has profound implications for his conception of politics and ontology. This reconsideration of Spinoza's political project, set within a historical context, lays the ground for an alternative genealogy of materialism.